The Development of Hypermedia-Based E-Module to Enhance Students' Creative Thinking Skills in the Topic of Digestive System for Junior High School Students (SMP/MTs) - Mohamad Khoirul Anam; Imam Mudakir; Jekti Prihatin (BIOEDUKASI, 2023)
The education system in Indonesia has undergone changes due to several factors such as 21st century education trends and the impact of the COVID-19 pandemic. These changes have resulted in a shift in student learning behavior towards different learning styles. With the end of the pandemic, students have returned to face-to-face learning, leading to the loss of certain learning behaviors adopted during the pandemic period. This, may result in a decrease in students' thinking ability. The purpose of this study is to develop hypermedia-based e-modules to improve students' creative thinking skills. The method used in this research is the Research and Development (R&D) method. This method follows the ADDIE model which consists of analysis, design, development, implementation, and evaluation. The development in this research includes hypermedia-based e-modules, learning instruments, creative thinking tests. The validity of the hypermedia-based e-module was assessed using the results of media validation. Effectiveness was measured by analyzing student and teacher responses. Effectiveness was determined through pre-test and post-test methods for creative thinking tests. The validation results showed "very valid" criteria with an average score of 95. Practicality, based on student and teacher responses in each session, obtained an average score of 90 with "very practical" criteria. Effectiveness, measured through a pre-test and the mean scores of the pre-test and post-test scores, showed values of 0.61, 0.55, and 0.56 for the small, large, and dispersed classes, with "medium" criteria. Creative thinking scores ranged from 80-90, indicating "very high" criteria. From these two results, it can be concluded that the hypermedia-based e-module on human digestive system material is valid, practical, and effective to improve the creativity of junior high school students.